Stress Buffering and Longevity Effects of Amber Extract on Caenorhabditis elegans (C. elegans) - Sandra Somuah-Asante; Kazuichi Sakamoto (Molecules, 2022)
Amber is a fossilized tree resin historically used in wound healing and stress relief. Unfortunately, there is no concrete scientific evidence supporting such efficacy. Here, the stress buffering and longevity effect of Amber extract (AE) in Caenorhabditis elegans (C. elegans) was investigated. Survival assays, health span assays, Enzyme-Linked Immunosorbent Assay (ELISA), Stress biomarker detection assays, Green Fluorescence Proteins (GFP), Real Time quantitative PCR (RT-qPCR) and C. elegans mutants were employed to investigate the stress buffering and longevity effect of AE. In the study, it was observed that AE supplementation improved health span and survival in both normal and stressed worms. Additionally, AE positively regulated stress hormones (cortisol, oxytocin, and dopamine) and decreased fat and reactive oxygen species (ROS) accumulation. Through the Insulin/IGF-1 signaling (IIS) pathway, AE enhanced the nuclear localization of DAF-16 and the expression of heat shock proteins and antioxidant genes in GFP-tagged worms and at messenger RNA levels. Finally, AE failed to increase the survival of daf-16, daf-2, skn-1 and hsf-1 loss-of-function mutants, confirming the involvement of the IIS pathway. Evidently, AE supplementation relieves stress and enhances longevity. Thus, amber may be a potent nutraceutical for stress relief.